2012
DOI: 10.3109/00365599.2012.696136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new PVC-free catheter material for intermittent catheterization: A prospective, randomized, crossover study

Abstract: Objective.Polyvinyl chloride (PVC) is commonly used as a catheter material in catheters for clean intermittent catheterization (CIC) but, owing mainly to environmental concerns, a PVC-free material has been proposed. The objective of this study was to compare patients' tolerability for catheters made of PVC and a newly developed PVC-free material. Material and methods.This was a prospective, randomized, crossover study in 104 male patients with maintained urethra sensibility who practised CIC. The patients eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Another limitation of the study was the use of a nonvalidated patient‐reported questionnaire for collection of the study variables. The selected questions were, however, based on previous findings from studies (e.g., (Johansson et al, )), experiences from product development, and clinical expertise. It is acknowledged that since the time point of the study, validated forms have been published that might have been suitable for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the study was the use of a nonvalidated patient‐reported questionnaire for collection of the study variables. The selected questions were, however, based on previous findings from studies (e.g., (Johansson et al, )), experiences from product development, and clinical expertise. It is acknowledged that since the time point of the study, validated forms have been published that might have been suitable for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Included patients were asked to fill out two questionnaires. The selection of questions in the patient‐reported questionnaires were based on previous findings from studies of similar catheters (e.g., (Johansson et al, )), experiences from product development from the manufacturer and clinical expertise. That is, during questionnaire development, content validity was considered by clinical experts part of the LoFric Origo study group.…”
Section: Methodsmentioning
confidence: 99%
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
“…17,24,25,30,35,38,[40][41][42] Seven articles out of nine reported a significant higher satisfaction and/or preference reported with hydrophilic catheter, when compared with non-hydrophilic catheters. 24,30,35,38,[40][41][42] However, two articles reported a nonsignificant difference in overall satisfaction. 17,25 Hydrophilic vs hydrophilic catheters.…”
Section: Patient's Satisfaction and Quality Of Lifementioning
confidence: 99%
“…Poly(vinyl chloride) (PVC) ( Figure 6) is a thermoplastic material with a melting point of around 240 • C. When PVC is plasticised, it can have some advantageous properties, such as good biocompatibility, flexibility, and strength, and has been used in biomedical applications for catheters, gloves, and blood bags [75]. Sharma et al has shown the effective extrusion of PVC granules into filaments, and further processed the PVC filaments through FDM [76].…”
Section: Poly(vinyl Chloride)mentioning
confidence: 99%